Investigation of absorption, metabolism, and excretion of [14C]pruxelutamide (GT0918), an androgen receptor antagonist in humans - Zheng, Yuan‐dong; Ma, Sheng; Yuan, Ya‐li; Zhang, Hua; Yang, Ying; Ye, Feng‐zhi; Wang, Mei‐yu; Chen, Jie; Tong, You‐zhi; Hu, Tao; He, Yi‐fei; Zhang, Yi‐fan; et al. (British journal of clinical pharmacology, 2025)
Aims The primary objective of this study was to determine the pharmacokinetics, mass balance and biotransformation of [14C]GT0918 in humans after the drug was administered to healthy Chinese male subjects. Methods The absorption, metabolism, and excretion (AME) of GT0918 was characterized via isotope labelling technology in six healthy Chinese male subjects after receiving a single 200 mg oral dose of [14C]GT0918 (80 μCi), and the phenotype, together with the metabolic mechanism of GT0918, was confirmed in vitro. Results The medium Tmax of total radioactivity was 6.00 h (4.00–8.00 h) post‐dose, and the mean Cmax was 10.5 μg eq./mL (8.7–12.3 μg eq./mL) in plasma. Drug‐related components in the plasma were eliminated slowly, with a mean t1/2 of 67.7 h (54.4–90.7 h), and the radioactivity of the plasma samples from some subjects was above the below the quantization limit (BQL) until 17 days post‐dose. After 19 days of dosing, the mean cumulative excreted radioactivity was 82.81% (79.07–86.07%) of the dose, including 29.47% (26.71–32.02%) in urine and 53.34% (52.01–55.62%) in faeces, indicating that the drug‐related components of GT0918 were mainly excreted by faeces. Metabolite profiling revealed that the parent drug was detected in plasma, as well as in faeces and not in urine. In plasma, the most abundant metabolite was GT0955, a mono‐oxidative metabolite of GT0918; in urine, the primary metabolite was GT0795, a metabolite of oxazole ring‐opening followed by N‐dealkylation; in faeces, the two main metabolites were M551 and the glucuronidation of GT0955. The majority of the metabolites were formed via an important aldehyde intermediate derived from the oxazole ring‐opening, and the intermediate was trapped by methoxyamine hydrochloride in the in‐vitro study. CYP3A4 is the main enzyme involved in the metabolism of GT0918. Conclusions Overall, all the dosed subjects completed the study, and GT0918 was found to be safe, with no grade II or above adverse events reported. A total dose of 82.81% was quantified in the urine (29.47%) and faeces (53.34%) of healthy adult male subjects after a single oral administration of 200 mg (80 μCi) GT0918 ([14C]GT0918). The metabolism of GT0918 is catalysed predominantly by CYP3A4, and an uncommon pathway of oxazole ring‐opening to an aldehyde intermediate has also been proposed.